Leave recommender mobile application for supporting staff of UiTM Malacca Campus Jasin / Maizeaitul Nasira Mohamad Haris - Mohamad Haris, Maizeaitul Nasira (2015)
Leave of absence is time allowed away from work which requested by an employee to cover unusual circumstances occurring in their life. Rapid development in technology enables things to be accessible through smartphone. Leave Recommender Mobile Application is designed to help recommending and handling the process in applying leave in a much more effective and efficient way. This system help to plan the employee leave by giving recommendation on the suitable date for applying leave. Besides, the systems can also handle leave application and reject or approve leave application. This system will be using Android as its platform. Mobile application development life cycles are adapted in this project in order to achieve the objectives. This project will give recommendation based on the rules by using rule based recommender system. Eight rules are used in this project and the rules are gathered from the interview with the expert in UiTM Jasin.